Problemy postępowania zabezpieczającego w sprawach cywilnych - Zedler, Feliks (Wydział Prawa i Administracji UAM, 1988)
The author criticizes the present solutions on the grounds that they are not adequate to the actual socio-economic conditions. In particular, injunction is not available in all civil cases and against all types of parties. The main part of the article sets forth the postulates as to the future changes in injunction proceedings. For example, the author suggests that injunction should be allowed in all civil cases and the forms of injunction should be more diversified than they are at present.
The problems of injunction proceedings in civil lav cases